Trudność zadania komunikacyjnego a bogactwo leksykalne wypowiedzi uczniów - Róg, Tomasz (Neofilolog, 2021)
Task-based language teaching has recently become a mainstream research area in second language acquisition studies. One of the underexplored areas is task design and its influence on the measures of complexity, accuracy, and fluency. While most previous research into task design focused on manipulating planning time, note-taking, or task familiarity, one of the promising lines of investigation is how task difficulty may also be conducive to L2 acquisition. Task difficulty is understood as the cognitive burden placed on a learner performing a task. In the current study learners of English as a foreign language (n=28) performed three differently designed oral communicative tasks of increasing difficulty: (1) a brainstorming task, (2) a sorting and ordering task, and (3) a problem-solving argumentative task. Task difficulty, i.e. having to employ higher-order thinking skills improved learners’ L2 lexical complexity as measured by lexical diversity, lexical density, and word-frequency counts.